Collective orientational order and phase behavior of a discotic liquid crystal under nanoscale confinement. Issue 3 (19th December 2018) - Yildirim, Arda; Sentker, Kathrin; Smales, Glen Jacob; Pauw, Brian Richard; Huber, Patrick; Schönhals, Andreas
Abstract : The phase behavior and molecular ordering of hexakishexyloxy triphenylene (HAT6) DLCs under cylindrical nanoconfinement, for nanopore diameters ranging from 161 nm down to 12 nm, are studied utilizing differential scanning calorimetry (DSC) and dielectric spectroscopy (DS). Abstract : The phase behavior and molecular ordering of hexakishexyloxy triphenylene (HAT6) DLCs under cylindrical nanoconfinement are studied utilizing differential scanning calorimetry (DSC) and dielectric spectroscopy (DS), where cylindrical nanoconfinement is established through embedding HAT6 into the nanopores of anodic aluminum oxide (AAO) membranes, and a silica membrane with pore diameters ranging from 161 nm down to 12 nm. Both unmodified and modified pore walls were considered. In the latter case the pore walls of AAO membranes were chemically treated with n -octadecylphosphonic acid (ODPA) resulting in the formation of a 2.2 nm thick layer of grafted alkyl chains. Phase transition enthalpies decrease with decreasing pore size, indicating that a large proportion of the HAT6 molecules within the pores has a disordered structure, which increases with decreasing pore size for both pore walls. In the case of the ODPA-modification, the amount of ordered HAT6 is increased compared to the unmodified case. The pore size dependencies of the phase transition temperatures were approximated using the Gibbs–Thomson equation, where the estimated surface tension is dependent on the molecular ordering of HAT6 molecules within the pores and upon their surface. DS was employed to investigate the molecular ordering of HAT6 within the nanopores. These investigations revealed that with a pore size of around 38 nm, for the samples with the unmodified pore walls, the molecular ordering changes from planar axial to homeotropic radial. However, the planar axial configuration, which is suitable for electronic applications, can be successfully preserved through ODPA-modification for most of the pore sizes.